2010
DOI: 10.1007/s11695-010-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

24-h pH-metry and Multichannel Intraluminal Impedance Monitoring in Obese Patients with and without Gastroesophageal Reflux Disease Symptoms

Abstract: Obese patients showed an increased number of refluxes with acid content. Refluxes with proximal extent were significantly higher in obese non-GERD than in controls and non-obese GERD patients. No difference was observed between the two obese patient groups. In asymptomatic obese patients, the WC correlated with proximal extent episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The prevalence of ERE in this same study was 18.7%, which was higher than that in the general population but lower than that in our sample (38.0%). 21 Similar to other studies, 5,21,27 our results showed a significant relationship (p=0.011) between BMI >35kg/m 2 and ERE. Furthermore, there was a significant correlation between ERE and the DeMeester score (p=0.028), and between ERE and transient LES relaxation (p=0.010), and the variables were strongly and positively correlated and varied simultaneously.…”
Section: Ugesupporting
confidence: 91%
“…The prevalence of ERE in this same study was 18.7%, which was higher than that in the general population but lower than that in our sample (38.0%). 21 Similar to other studies, 5,21,27 our results showed a significant relationship (p=0.011) between BMI >35kg/m 2 and ERE. Furthermore, there was a significant correlation between ERE and the DeMeester score (p=0.028), and between ERE and transient LES relaxation (p=0.010), and the variables were strongly and positively correlated and varied simultaneously.…”
Section: Ugesupporting
confidence: 91%
“…According to our study, non-acid reflux does not play a role in the relationship between GER and sleep quality in obese children. This is consistent with the report that obese patients have more AGER and GERD but not non-acid reflux as compared to healthy volunteers [ 12 ]. Adult studies showed that a painful stimuli from acid reflux can be associated with arousals and brief awakenings as a protective mechanism, generating secondary peristalsis and facilitating acid clearance.…”
Section: Discussionsupporting
confidence: 93%
“…A higher prevalence of gastroesophageal reflux disease (GERD) and its complications have also been reported in obese patients [ 12 ]. The association of obesity and gastroesophageal reflux (GER) is reported with an odds ratio of 7.3 (95% CI 1.7-31.0) [ 13 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies exist in literature reporting data of the use of 24h MIIpH in obese individuals, but none of them reports normal values. A study from Ricci et al reported increased acid reflux episodes in obese symptomatic and asymptomatic individuals in comparison to non-obese healthy individuals [19]. Recently, Akyuz et al reported the results of 24h MIIpH in asymptomatic obese subjects revealing a positive correlation between BMI and the number of reflux episodes [20].…”
Section: Discussionmentioning
confidence: 97%